Environmental liabilities in insolvency – an area ripe for reform?. Issue 3 (10th October 2016) - Mamutse, Blanca
Abstract : Purpose: The paper aims to examine the question whether legislative reform is the silver bullet for the problems generated by the failure of a company which is exposed to claims arising from the non-fulfilment of its environmental obligations. The limited capacity of the UK insolvency regime to facilitate the fulfilment of a debtor company's environmental obligations is often illustrated with reference to some significant judicial decisions. However, no real picture has emerged of the frequency with which these issues arise, based on which firm proposals for reform could be advanced. This paper argues that greater regard should be paid to existing mechanisms which provide a means of enabling insolvency risks to be managed or minimised because these point towards the scope for these issues to be resolved through the environmental protection framework rather than through reliance on company and/or insolvency law. Design/methodology/approach: Research was conducted into the statutory and non-statutory regulations (such as statutory guidance) and case law principles, which underpin the treatment of the claims against an insolvent (or potentially insolvent) company resulting from its environmental activities. This included research into policies which have a bearing on this area, developed through governmental and civic consultations and studies. Findings: The paper concludes that the likelihood of a case for legislative reform being made out is weak, and the focus should accordingly shift to strengthening the effectiveness of existing law, policy and practice. Originality/value: This paper is the first (in the UK context) to challenge the perceived need for reform in this area, engaging with recent examples of such corporate failures and the impact of recent legislative and policy developments.